ATRT-07. MURINE SOX2-POSITIVE EARLY PRECURSOR CELLS GIVE RISE TO RHABDOID TUMORS WITH FEATURES OF THE HUMAN ATRT-MYC GROUP. Issue 2 (22nd June 2018) - Galarza, Natalia Moreno; Holdhof, Dörthe; Interlandi, Marta; Melcher, Viktoria; Graf, Monika; Kastrati, Dennis; Meisterernst, Michael; Johann, Pascal; Kool, Marcel; Frühwald, Michael; Schüller, Ulrich; Kerl, Kornelius
Abstract: PURPOSE: Atypical teratoid rhabdoid tumors (ATRT), characterized by SMARCB1 loss, have been classified by DNA methylation and gene expression profiling into three distinct molecular subgroups (ATRT-SHH, -MYC, -TYR). We hypothesize that ATRT from distinct subgroups have a different cell of origin. METHODS: Multiple precursor cell specific, constitutive and inducible Smarcb1 knockout mouse strains were established by using a Cre-loxP system. Murine tumors were analyzed by histology and gene expression profiling. Unsupervised hierarchical clustering and differential expression analyses were performed. RESULTS: Rhabdoid tumor (RT) development was detected only when Smarcb1 abrogation occurred in a very restricted time frame during embryonic development and only under the control of an ubiquitous (Rosa26) or Sox2 promoter. Unsupervised hierarchical clustering of Affymetrix gene expression profiles of these murine and of published human ATRT classified tumors of the Rosa26cre ERT2 ::Smarcb1 Fl/Fl model either as ATRT-MYC or as ATRT-SHH. In contrast, ATRT of Sox2cre ERT2 ::Smarcb1 Fl/Fl mice were assigned to the ATRT-MYC subgroup only. Mouse strains in which the Smarcb1 knockout was driven by Nestin-, hGFAP -, Math1 -, Olig1 - Cre recombinase presented other phenotypes but not RT. CONCLUSION: Subgroup-specific RT genesis depends on the cell of origin. Here we identify early Sox2-positive progenitors as precursor cells of ATRT-MYC subgroup. We further demonstrate that Smarcb1 abrogation during a specific, short time period and in a specific targeted cell population is crucial for induction of ATRT-MYC.